Simulations of interaction between PMDs (personal mobility devices) and pedestrians - Ang, Christopher Gao Qian (2019)
Every day, students from NTU would travel on the internal shuttle bus service. In this report it summarises the author’s progress and learning pointers during his Final Year Project, “Simulations of Interaction between PMDs (Personal Mobility Devices) and Pedestrians” under the supervision of Associate Professor Justin Dauwels.